Pengukuran Kecepatan Kendaraan Secara Realtime Berbasis Android - Gustina, Rendi; Setiawan, Widyadi; Indra ER, Ngurah (Majalah Ilmiah Teknologi Elektro, 2016)
Abstract— Intelligent transport systems in the android operating system is able to bring about change is very important in human life. Objectives and benefits in this thesis is to obtain an application program measuring the speed of vehicles in real time based on Android using the Frame Difference and Bounding Box wearing reference distance, the vehicle speed of 10 km / h, 20 km / h and 30 km / h and distance 6 meters. After getting the average speed of vehicles, will be calculated deviation measurements of vehicle speed and the actual results compared to the average. For the measurement of the speed of vehicles put on the vehicle speed measurement applications in realtime based on android gained an average of 20.572 km / h with a maximum deviation 0.572 km / h and an average of 29.688 km / h with minimal deviation 0.312 km / h. For the measurement of the speed of vehicles put on the analysis of vehicle speed measurement in digital video recording obtained by an average of 31.454 km / h with a maximum deviation 1,454 km / h and an average of 10.112 km / h with minimal deviation 0.112 km / h.
Keywords: Android, Kecepatan Kendaraan, Frame Difference, Bounding Box